Karyotype of Four Malayan Rats (Muridae, Genus Rattus Fischer) - Yong, Hoi Sen (Japan Mendel Society, 1968)
A great deal of information concerning the Malayan rats (Muridae, genus Rattus Fischer) exists in the literature. However there is no report on the karyotype of these rats. Karyotype information of wild rats in other parts of the world exists, but is scanty. Makino (1942, 1943, 1949b, 1952c) studied six species of Rattus found in Japan. Most other studies have been confined to Rattus norvegicus albino (Tanaka 1953, Makino and Hsu 1954). The techniques employed in the earlier studies were not sufficiently refined to permit critical analysis. A more recent paper is that of Tanaka and Kano (1957) on R. norvegicus albino. The present paper deals with four species of Malayan rats. They are Rattus bowersii Anderson, R. muelleri Jentink, R. edwardsi Thomas, and R. sabanus Thomas. According to Chasen (1940) as modified by Ellerman and Morrison-Scott (1956), the Malayan mainland forms for these species are R. b. ferreocanus Miller, R. m. validus Miller, R. e. ciliatus Bonhote, and R. s. vociferans Miller.